2022
DOI: 10.1038/s41598-021-04752-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of feeding behaviour traits in response to production environment (temperate vs. tropical) in group-housed growing pigs

Abstract: Heat stress affects pig metabolism, health and welfare, resulting in reduced growth and important economic losses. The present experiment aimed to evaluate the effects of two climatic environments [temperate (TEMP) vs. tropical humid (TROP)] on feeding behaviour in growing pigs. The feeding behaviour traits were measured with automated feeders and included: daily feed intake, daily eating time, feeding rate, daily number of meals, feed intake per meal, and feeding time per meal. Pigs came from a backcross popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Recently, it has been suggested that heat stress has various effects on pigs at the transcriptome and proteome levels (e.g., He et al, 2020 ; Pearce et al, 2015 ; Zhao et al, 2021 ) and that heat stress might have multi‐generational effects (Johnson et al, 2020 ). Studies to identify indicators of heat stress (e.g., Cross et al, 2018 ; Gourdine et al, 2019 ; Poullet et al, 2022 ) and those for predicting breeding values for heat tolerance using public weather data (e.g., Tiezzi et al, 2020 ; Usala et al, 2021 ; Zumbach et al, 2008 ) have also been performed. Thus, developing methodology to genetically improve pigs to cope with climate change would be valuable (e.g., Gourdine et al, 2021 ; Hara et al, 2022 ; Ogawa, Kimata, et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been suggested that heat stress has various effects on pigs at the transcriptome and proteome levels (e.g., He et al, 2020 ; Pearce et al, 2015 ; Zhao et al, 2021 ) and that heat stress might have multi‐generational effects (Johnson et al, 2020 ). Studies to identify indicators of heat stress (e.g., Cross et al, 2018 ; Gourdine et al, 2019 ; Poullet et al, 2022 ) and those for predicting breeding values for heat tolerance using public weather data (e.g., Tiezzi et al, 2020 ; Usala et al, 2021 ; Zumbach et al, 2008 ) have also been performed. Thus, developing methodology to genetically improve pigs to cope with climate change would be valuable (e.g., Gourdine et al, 2021 ; Hara et al, 2022 ; Ogawa, Kimata, et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to Poullet et al [ 30 ], the upper limit of thermoneutrality, in which no extra energy is used for thermoregulation, ranges between 20 °C and 25 °C for growing–finishing pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced FI and increased body temperature have been widely described as related to HS. In terms of feeding behavior, the animals have more meals per day, but of shorter duration and in smaller quantities, a nibbling/slow eating pattern [ 4 , 5 , 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%